In Efforts to Improve Online-Based Services (Case study at the One-Stop Integrated Service Investment Office (DPMPTSP) of Jepara Regency) - Rahmawati, Luluk; Andni , Riyan; Faza, Iqbal (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Background. In today's era, easy access to the use of technology and information is a flow of global components where it all cannot be separated by the modernity of society, the number of gadget users proves that the ease of access to technology and information in services is growing rapidly. The availability of various characteristic services on the gadget is a facility for technology users, it can also help each individual in completing various forms of work.. Purpose. This study aims to analyse the effectiveness of e-government implementation in licensing services at DPM-PTSP Jepara Regency. Method. This type of research is descriptive qualitative with data collection techniques using observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and conclusion drawing. Results. The results of this study state that with the launch of the official DPMPTSP website, it is hoped that the implementation of licensing services will no longer take months but only hours, but DPMPTSP must be able to make more efforts because there are still several obstacles in the implementation of e-government. Conclusion. the conclusion of this research is that the launch of the official website portal from DPMPTSP, hopefully the application of licensing services will no longer take days but only hours and service delivery can continue to strive for progress as well as growth so that the community, especially business people, can fulfil their various rights and basic needs. therefore the implementation of One Stop Integrated Services (PTSP) regarding OSS licensing, JOSS and SIMBG making can be said to simplify the bureaucracy and make it easier for business actors.